Human acellular dermal wound matrix: evidence and experience. Issue 6 (28th November 2013) - Kirsner, Robert S; Bohn, Greg; Driver, Vickie R; Mills, Joseph L; Nanney, Lillian B; Williams, Marie L; Wu, Stephanie C
Abstract: A chronic wound fails to complete an orderly and timely reparative process and places patients at increased risk for wound complications that negatively impact quality of life and require greater health care expenditure. The role of extracellular matrix (ECM) is critical in normal and chronic wound repair. Not only is ECM the largest component of the dermal skin layer, but also ECM proteins provide structure and cell signalling that are necessary for successful tissue repair. Chronic wounds are characterised by their inflammatory and proteolytic environment, which degrades the ECM. Human acellular dermal matrices, which provide an ECM scaffold, therefore, are being used to treat chronic wounds. The ideal human acellular dermal wound matrix (HADWM) would support regenerative healing, providing a structure that could be repopulated by the body's cells. Experienced wound care investigators and clinicians discussed the function of ECM, the evidence related to a specific HADWM (Graftjacket ® regenerative tissue matrix, Wright Medical Technology, Inc., licensed by KCI USA, Inc., San Antonio, TX), and their clinical experience with this scaffold. This article distills these discussions into an evidence‐based and practical overview for treating chronic lower extremity wounds with this HADWM.